Some Aspects of Assessing Investment Attractiveness in the Digital Economy (Texas Journal of Multidisciplinary Studies, 2022)
This article talks about the dependence of the country's economy, improving living conditions and increasing incomes of the population, in a word, socio-economic stability mainly on the volume and composition of investments in various sectors and sectors of the national economy.And therefore, the creation of an attractive environment for attracting investment in the national economy should become a priority in the strategy of socio-economic development of each country. It should be noted that at the present stage of development of the world community, no country, even a developed one, can achieve socio-economic development without investment.